Assessing RFMIS Implementation Using DeLone and McLean Model: En-hancing Regional Financial Management - Limerick, Ashill; Zambrano, Padigar Wixom; Carley, Carley (Law and Economics, 2023)
This research study focuses on assessing the implementation and effectiveness of Regional Financial Management Information Systems (RFMIS) within the context of regional governance. Employing the DeLone and McLean Model dimensions, the research aims to comprehensively analyze the system's impact on financial management practices and its significance within regional governance structures. By examining user perceptions and system performance, the study evaluates the strengths, weaknesses, and the implications of RFMIS implementation. Key findings reveal the importance of system quality, information accuracy, user satisfaction, and service quality as pivotal determinants of the system's success. The study emphasizes the RFMIS's role in improving decision-making, transparency, and operational efficiency in regional financial management. Furthermore, the research highlights identified weaknesses in user interface, support services, system maintenance, and adaptability, signifying areas necessitating immediate attention for improvement. The implications of this research extend beyond regional financial management, emphasizing the broader transformative potential of information systems in promoting transparency, enhancing governance, and driving positive outcomes. Addressing the identified weaknesses presents opportunities for better system performance and user satisfaction, contributing to the continued advancement of effective information systems within regional governance. This study's insights emphasize the importance of continued investment, user-centric design, and ongoing adaptation in information systems, setting a precedent for effective governance practices and technological innovation across various sectors.